2019
DOI: 10.1590/1980-5373-mr-2018-0820
|View full text |Cite
|
Sign up to set email alerts
|

Application of Zinc Oxide in Hybrid Solar Cells Using a P3HT and P3OT Polymer Junction as Charge Carrier

Abstract: Hybrid solar cells show an increasing number in researches due to its low cost and easy of production. They are composed by and organic material and a semiconductor oxide. The aim of this paper was to synthesis and characterize zinc oxide by coprecipitation and apply it in a hybrid solar cell that uses a P3HT/P3OT copolymer as charge carrier. The cell was assembled in "sandwich" form using FTO/ ZnO/P3HT-P3OT as work electrode, (Pt/FTO) as conter electrode and I/I-3 redox couple as electrolyte. Through the X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…The nanoparticles prepared from ZnSO 4 in the present study have a similar configuration in terms of shape and size as found in previous studies (Nair et al, 2009;Larsson et al, 2019;PP, 2020;Tymoszuk and Wojnarowicz, 2020;Mahmood et al, 2021;Patella et al, 2022). The nanoparticles seen the in scanning electron micrographs were well separated, with negligible agglomeration, which is similar to the results of Umar et al (Umar et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
“…The nanoparticles prepared from ZnSO 4 in the present study have a similar configuration in terms of shape and size as found in previous studies (Nair et al, 2009;Larsson et al, 2019;PP, 2020;Tymoszuk and Wojnarowicz, 2020;Mahmood et al, 2021;Patella et al, 2022). The nanoparticles seen the in scanning electron micrographs were well separated, with negligible agglomeration, which is similar to the results of Umar et al (Umar et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
“…Zinc Oxide (ZnO) is a multifunctional material [1,2] with semiconducting properties (p-type, band gap of 3.37 eV) [3,4] that is used in many advantageous applications from biomedical field, to electrical and electronics industry and energy conversion [5][6][7]. It is a cheap and biocompatible material widely used for production of paints, rubber, plastic and pharmaceuticals [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Zinc Oxide (ZnO) is a transparent p-type semiconductor with a band gap of 3.37 eV [1,2] with many advantageous applications in electrical and electronics industry, such as for solar cells [3][4][5]. In addition, it is a cheap and biocompatible material widely used in many industrial fields, such as production of paints, rubber, plastic and pharmaceuticals [6,7].…”
Section: Introductionmentioning
confidence: 99%